Delay in COVID-19 Vaccinations: The Role of Travel Time to Vaccine Sites - Yuxia Huang; Jim Lee (COVID)
Introduction: A growing body of literature has identified a variety of factors affecting vaccine uptake, but the role of geographic accessibility remains unclear. This study fills this knowledge gap by empirically investigating the extent to which the time driving to vaccine sites as a measure of geographic friction affected COVID-19 vaccine uptake. Methods: A logistic model and a hazard-based duration model were applied to the official data of more than 142,000 adults who took at least one COVID-19 vaccine in Nueces County, Texas, between December 2020 and August 2022. Using the street network, travel time was calculated from individuals’ home addresses to the addresses of the sites where they received their vaccinations. Results: The logistic model indicated that individuals living farther from vaccine sites were less likely to receive full vaccination, controlling for their sociodemographic characteristics that affected vaccine hesitancy. The duration model further showed that fully vaccinated persons would delay a booster shot longer if they had to travel longer for a vaccine. Conclusions: To the extent that the health protection of a COVID-19 vaccine declines over time, the integration of spatial and temporal dimensions in the duration model allowed us to shed light on the relationship between travel time and delay in booster vaccination. A vaccination campaign should make vaccination services physically convenient for vaccine recipients from different communities.